Implementation of patient-centered care in transforming mental health services: A scoping review - Ariyani, Peni; Jiu, Cau Kim; Lestari, Lilis; Jais, Suriadi; Haryanto, Haryanto (Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Unit Penelitian dan Pengabdian Kep Akademi Keperawatan Baitul Hikmah, 2026)
Background: Global healthcare is shifting from a traditional paternalistic model to a more inclusive and collaborative approach through Patient-Centered Care (PCC). While its impact on efficiency and patient satisfaction is well-documented, a gap remains in mapping how PCC acts as a catalyst for organizational and cultural transformation in hospitals, especially during digital transitions. Purpose: To map and synthesize existing evidence regarding the implementation of patient-centered care in transforming mental health services. Method: Following the Arksey and O’Malley framework, a systematic search was conducted on PubMed, ScienceDirect, and Wiley Online Library for articles published between 2015 and 2025. After rigorous screening, 10 articles met the inclusion criteria and were used for data synthesis. Results: The findings identify three primary transformation themes: (1) Digital Transformation, utilizing virtual care, 3D medical imaging, and eHealth to enhance patient empowerment; (2) Cultural and Behavioral Transformation, focusing on therapeutic engagement and transparent communication; and (3) Structural Transformation, requiring collaborative governance and distributed leadership. Key facilitators include senior leadership support and change agents, while staff resistance and digital literacy remain significant barriers. Conclusion: Hospital transformation through PCC requires a holistic approach that balances technological advancement with human-centered care. Success depends on strong policy support and a leadership model that embraces all medical professions to ensure sustainable service optimization. Keywords: Hospital Service; Patient-Centered Care; Transformation.